Emulsification and stabilization of diacylglycerol-in-water pickering emulsions stabilized by ultrafine grinding oat bran insoluble fiber-gelatinized starch hybrid granules. (March 2021) - Xue, Xiuheng; Dong, Jinhua; He, Haiyong; Wang, Juhua; Kong, Derui; Wang, Liwen
Abstract : In this work, the hybrid granules with oat bran insoluble fiber and gelatinized starch were prepared and used as stabilizers for diacylglycerol (DAG) Pickering emulsions. Adsorption capacity, emulsification and digestion stability of DAG Pickering emulsions were evaluated. The results show that DAG Pickering emulsions were prepared by using ultrafine grinding oat bran insoluble fiber-gelatinized starch hybrid granules as surface stabilizer. The hybrid granules containing gelatinized starch and oat bran insoluble fiber can be adsorbed on the DAG surface when average particle size was less than 4.38 μm. The content of oat bran insoluble fiber in the hybrid granules played an important role in the increase of surface zeta potential and hydrophilicity, which can lead to the increase of adsorption capacity and stabilization of the Pickering emulsions. With increasing of the oat bran insoluble fiber in the hybrid granules from 20% to 80%, the droplet dispersion, adsorption capacity, and emulsion stability of the DAG Pickering emulsions were increased gradually, while the final FFA released showed decreased tendency during the simulated gastrointestinal digestion. The emulsion index was 74.2% and the average droplet size was about 22.90 μm when the pH was 8 and oat bran insoluble fiber content in the hybrid granules was 60%, and the DAG Pickering emulsions remained stability for 5 days at 25 °C. The oat bran insoluble fiber coated with gelatinized starch was better to be used as stabilizers to improve the emulsification and digestion stability of lipid Pickering emulsions. Graphical abstract: The diacylglycerol (DAG) Pickering emulsions were prepared by using ultrafine grinding oat bran insoluble fiber-gelatinized starch hybrid granules as surface stabilizers. With increasing of the oat bran insoluble fiber in the hybrid granules from 20% to 80%, the droplet size distribution, surface zeta potential, adsorption capacity, and emulsion stability of the DAG Pickering emulsions were increased gradually, while the final FFA released showed decreased tendency during the simulated gastrointestinal digestion. The emulsion index was 74.2% and the average droplet size was about 22.90 μm when the pH was 8 and oat bran insoluble fiber content in the hybrid granules was 60%, and the DAG Pickering emulsion remained stability for 5 days at 25 °C. The oat bran insoluble fiber-gelatinized starch hybrid granule was better to be used in Pickering emulsions for the design of coatings systems to improve the stability of Pickering emulsions. Image 1 Highlights: DAG Pickering emulsions stabilized by oat bran insoluble fiber-gelatinized starch were prepared. The hybrid granule containing gelatinized starch and fiber can be adsorbed on the DAG surface. The oat bran insoluble fiber-gelatinized starch was better to be used as stabilizers of DAG emulsion. DAG stabilized by oat bran insoluble fiber-gelatinized starch has good emulsification. DAG digestion stability can be improved by oat bran insoluble fiber-gelatinized starch as stabilizer.